PREVALENSI EKTOPARASIT PADA POPULASI ANJING PELIHARAAN (Canis lupus familiaris) DI KOTA PAYAKUMBUH - Nalitha, Faradisa Firsty; Mahatma, Radith; Muhammad, Ahmad (2016)
The close relationship between domestic dogs and man implies the importance of the health care of the pets. One of the parameters of dog’s health is the presence of ectoparasites. Payakumbuh is a town in West Sumatra, where the dog keeping is very popular among the residents. The present study aimed to know ectoparasite species found in the domestic dog population at this town and assess their prevalence in the population. It also attempted to obtain indications of the influence of dog’s race, sex and raising conditions on ectoparasite prevalence. A total of 50 domestic dogs were examined and the presence of ectoparasites was demonstrated in 44% of the dogs with an intensity of 3,6 ectoparasite individuals/dog. Only two ectoparasite species were found, i.e. Ctenocephalides canis and Rhipicephalus sanguineus. The prevalence of the former was more dominant (38%) then that of the later (6%). It appeared that the dog’s vulnerability to ectoparasites was more influenced by raising conditions than by the race, sex, and age of the animal Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Riau